PENGEMBANGAN MODEL PEMBELAJARAN REFLEKTIF UNTUK PEMAHAMAN KONSEP DEMOKRASI PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Lastinah Lastinah; Indri Astuti; Andy Usman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe background of this study is learners find difficulty to understand abstract concepts; therefore it needs a concrete operational stage in the material of democracy. The purpose of this study is to describe the design, implementation and knowing the learning achievement  of  learners  after  using  reflective  learning  model  for  understanding  the concept of democracy in the subjects of civic education. This type of research uses research & development.. Learning model development system refers to the ten stages of development. Techniques of collecting data as follows: direct observation techniques, interviews, documentation and test. Data analysis (interactive model) uses Miles and Huberman model. The results of the study as follows. (1) The design of the development of reflective learning models that include instructional design and storyboard is worthy of use in the learning process.  (2)  Implementation  of  model  development  through  several  stages,  namely material expert validation, media, design, and testing. The average score of validation results of 3.21 categories is very clear so that the product is declared worthy of use in learning. (3) Student learning outcomes after using reflective learning model and student book product increased by 33.33% one-to-one test, 41.81% small group test and 44.79% for large group.Key Word : Reflective Learning Model